FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR IPS TERPADU SISWA KELAS VII MTSN 1 LUBUK BASUNG - Afriyeni, Riri; Suarto, Edi; Iswandi U, Iswandi U (STKIP PGRI Sumbar, 2013)
This research aims to determine the influence of learning motivation and learning environments on learning outcomes of students class VII Integrated Social Science of MTsN 1 Lubuk Basung. This research is descriptive associative research. The population was students Â class VII of MTsN 1 Lubuk Basung as many as 147 students. To determine the sample size used sampling techniques conducted by proportional random sampling with a proportion of 50%. The sample size of 75 students. The data collection technique used was a questionnaire. The data analysis technique used is descriptive analysis and to test the hypothesis used multiple regression F test and t test. The results of this research indicate that (1) There is significant relationship between learning motivation on learning outcomes of students class VII Integrated Social Science MTsN 1 Lubuk Basung by 20.9%. (2) There is a significant relationship between learning environments on learning outcomes of students class VII Integrated Social Science of MTsN 1 Lubuk Basung of 16.9% and (3) There is a significant relationship between learning motivation and learning environment jointly on learning outcomes Integrated Social Science of class VII of MTsN 1 Lubuk Basung of 34.2%.